Pteropine orthoreovirus of Bat Origin: An Emerging Pathogen Associated with Cases of Acute Respiratory Infections - Chan, Po Qhuan; Chook, Jack Bee *; Sam, I-Ching; Chan, Kok Gan; Voon, Kenny; Tee, Kok Keng (Elsevier, 2022)
Purpose Pteropine orthoreovirus (PRV) is a bat-borne virus classified under the Reoviridae family. It is a recently emerging virus in Southeast Asia and has been associated with sporadic respiratory infections in humans. Despite its epidemic potential, PRV is often neglected during diagnosis for acute respiratory infection (ARI) and may be accountable for cases of unexplained ARI. The study aims to assess the molecular prevalence and analyze the genetic diversity of PRV in patients with ARI in an urban population.